Physiological characterization of the tomato cutin mutant cd1 under salinity and nitrogen stress - Bonarota, Maria-Sole; Kosma, Dylan; Barrios-Masias, Felipe H. (Planta, 2024)
Main conclusion We identified tomato leaf cuticle and root suberin monomers that play a role in the response to nitrogen deficiency and salinity stress and discuss their potential agronomic value for breeding. The plant cuticle plays a key role in plant–water relations, and cuticle’s agronomic value in plant breeding programs is currently under investigation. In this study, the tomato cutin mutant cd1 , with altered fruit cuticle, was physiologically characterized under two nitrogen treatments and three salinity levels. We evaluated leaf wax and cutin load and composition, root suberin, stomatal conductance, photosynthetic rate, partial factor productivity from applied N, flower and fruit number, fruit size and cuticular transpiration, and shoot and root biomass. Both nitrogen and salinity treatments altered leaf cuticle and root suberin composition, regardless of genotype ( cd1 or M82). Compared with M82, the cd1 mutant showed lower shoot biomass and reduced partial factor productivity from applied N under all treatments. Under N depletion, cd1 showed altered leaf wax composition, but was comparable to the WT under sufficient N. Under salt treatment, cd1 showed an increase in leaf wax and cutin monomers. Root suberin content of cd1 was lower than M82 under control conditions but comparable under higher salinity levels. The tomato mutant cd1 had a higher fruit cuticular transpiration rate, and lower fruit surface area compared to M82. These results show that the cd1 mutation has complex effects on plant physiology, and growth and development beyond cutin deficiency, and offer new insights on the potential agronomic value of leaf cuticle and root suberin for tomato breeding.